2013
DOI: 10.1096/fj.12-224899
|View full text |Cite
|
Sign up to set email alerts
|

TIMP‐1 inhibits the proteolytic processing of Reelin in experimental epilepsy

Abstract: Temporal lobe epilepsy is frequently associated with granule cell dispersion (GCD), an abnormal widening of the granule cell layer in the dentate gyrus. There is increasing evidence that a loss and the functional inactivation of the positional signal Reelin is involved in GCD formation. Reelin is synthesized and released by Cajal-Retzius cells and interneurons, and its function depends on proteolytic cleavage after secretion. Epileptic conditions impair Reelin processing by inhibition of matrix metalloprotease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
35
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 44 publications
4
35
0
Order By: Relevance
“…However, these mechanisms only serve to adjust the level of reelin signaling, as they are not sufficient to initiate the reelin signal by themselves. In support of this view, preventing extracellular proteolysis of reelin by inhibiting metalloproteinases blocks signaling in the developing cortex and disrupts corticogenesis (Lambert de Rouvroit et al, 1999; Jossin et al, 2007) and also impairs reelin processing in an epilepsy model (Tinnes et al, 2013). These findings imply that reelin is tethered to the extracellular matrix following secretion, where it remains inactive until liberated by proteolysis to initiate downstream signaling.…”
Section: Introductionmentioning
confidence: 94%
“…However, these mechanisms only serve to adjust the level of reelin signaling, as they are not sufficient to initiate the reelin signal by themselves. In support of this view, preventing extracellular proteolysis of reelin by inhibiting metalloproteinases blocks signaling in the developing cortex and disrupts corticogenesis (Lambert de Rouvroit et al, 1999; Jossin et al, 2007) and also impairs reelin processing in an epilepsy model (Tinnes et al, 2013). These findings imply that reelin is tethered to the extracellular matrix following secretion, where it remains inactive until liberated by proteolysis to initiate downstream signaling.…”
Section: Introductionmentioning
confidence: 94%
“…Molecularly, such aberrant cellular positioning following perturbation of MMP proteolysis may reflect critical, early roles of MMPs in processing the secreted glycoprotein Reelin. Reelin is necessary for proper neuronal migration and lamination in hippocampus and other cortical structures (Tissir and Goffinet, 2003) and undergoes significant extracellular proteolytic processing by several different metalloproteinases for full bioactivity in vivo (Lambert de Rouvroit et al, 1999;Jossin et al, 2007;Tinnes et al, 2011Tinnes et al, , 2013Hisanaga et al, 2012;Krstic et al, 2012).…”
Section: Peak Expression During First Postnatal Weekmentioning
confidence: 99%
“…However, TIMP-1 KO mice were resistant to kainate-induced excitotoxicity. Recently, Tinnes et al (2013) reported that a seizure-induced increase in TIMP-1 interfered with normal proteolytic processing of reelin in the epileptogenic hippocampus, leading to granule cell dispersion. Electroconvulsive shock upregulates the TIMP-1, TIMP-2, and TIMP-4 transcription in the hippocampus (Girgenti et al, 2011).…”
Section: Matrix Metalloproteinases In Epileptogenesis and Epilepsymentioning
confidence: 99%